Dantas Mota e Mário de Andrade: entre a correspondência, as anotações marginais e a poesia - Almeida, Ana Elisa Tonetti de (2021)
Based on Pino & Zular's (2007) contributions to Genetic Criticism; on Sandra Nitrini's (2000) reflections concerning Comparative Literature, as well as in Michel Collot's (2013) studies on the poetics and philosophy of landscape, this paper focuses on the dialogue that is established between the writer José Dantas Mota, from Minas Gerais, and Mário de Andrade, from São Paulo, perceived through the correspondence between the two, the marginal notes present in the volume Surupango: ritmos caboclos (1932), by Dantas Mota, part of the São Paulo writer's library, as well as in poems by the Minas Gerais writer, marked by the relationship with the author of Pauliceia desvairada. Therefore, we aim to study the construction of Dantas Mota's poetry in Surupango and in some poems of Elegias do país das gerais (1988), identifying the influences that the poet from Minas Gerais received from Mário de Andrade in relation to the construction of poetic landscapes, music, and popular culture. Thus, we assume that the letters they both exchanged significantly influenced Dantas's artistic composition. The research is developed from the study of Dantas Mota's unpublished letters, located in Mário de Andrade's collection, available at the Institute of Brazilian Studies (IEB-USP), and the letters of the São Paulo writer published in the volume of complete poems Elegias do país das gerais, by Dantas Mota, as well as the notes of Mário de Andrade, in the 1932 copy, part of his personal library, which is part of his collection at the IEB-USP. In addition, comparative readings are made of poems by Dantas Mota and Mário de Andrade, chosen because they focus on themes relevant to both: landscapes, music and popular culture, since these elements bring them together.